2009
DOI: 10.1038/onc.2009.204
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine semaphorin 3A signaling promotes glioblastoma dispersal

Abstract: Glioblastoma multiforme (GBM) is the most malignant glioma type with diffuse borders due to extensive tumor cell infiltration. Therefore, understanding the mechanism of GBM cell dispersal is critical for developing effective therapies to limit infiltration. We identified neuropilin-1 as a mediator of cancer cell invasion by a functional proteomic screen and showed its role in GBM cells. Neuropilin-1 is a receptor for semaphorin3A (Sema3A), a secreted chemorepellent that facilitates axon guidance during neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
83
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 54 publications
6
83
0
1
Order By: Relevance
“…Long-term analysis of pTM-NRP1 membrane incorporation using confocal microscopy revealed cell-surface clearance of peptide after 96 h (data not shown). Consistent with our previous description of the action mechanism of the peptide (Roth et al, 2008), we found in C6 cells that pTM-NRP1 altered oligomerization of NRP1 on addition of Sema3A (Figure 5a), a semaphorin involved in glioma migration (Nasarre et al, 2009) and shown to promote glioma dispersal through an autocrine mechanism (Bagci et al, 2009). Moreover, although not inducing acute toxicity in C6 cells (see Figure 5b), the addition of pTM-NPR1 induced a significant reduction of cell proliferation (À32%, Po0.05, Figure 5c).…”
Section: Ptm-nrp1 Is An Anti-angiogenic Agentsupporting
confidence: 92%
See 1 more Smart Citation
“…Long-term analysis of pTM-NRP1 membrane incorporation using confocal microscopy revealed cell-surface clearance of peptide after 96 h (data not shown). Consistent with our previous description of the action mechanism of the peptide (Roth et al, 2008), we found in C6 cells that pTM-NRP1 altered oligomerization of NRP1 on addition of Sema3A (Figure 5a), a semaphorin involved in glioma migration (Nasarre et al, 2009) and shown to promote glioma dispersal through an autocrine mechanism (Bagci et al, 2009). Moreover, although not inducing acute toxicity in C6 cells (see Figure 5b), the addition of pTM-NPR1 induced a significant reduction of cell proliferation (À32%, Po0.05, Figure 5c).…”
Section: Ptm-nrp1 Is An Anti-angiogenic Agentsupporting
confidence: 92%
“…This is reflected by a strong reduction of the tumour bulk and lack of tumour cell dissemination. A recent study shows that Sema3A stimulates glioma cells dispersal by an autocrine mechanism (Bagci et al, 2009). Thus, it is tempting to speculate that the observed reduction of tumour growth and dissemination in the presence of pTM-NRP1 is the consequence of the inhibition of this mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…Although accumulating evidence has demonstrated a correlation between semaphorin expression and glioma progression (Correa et al, 2001;Rieger et al, 2003;Rich et al, 2005), studies of the expression of plexins and the role of semaphorin-plexin interactions in gliomas remain scanty (Rieger et al, 2003;Bagci et al, 2009;Nasarre et al, 2009;Coma et al, 2010). Here, we show that plexin-B3 is expressed in human glioma cells, which upon activation by its ligand Sema5A inhibits cell motility, triggers cell collapse and promotes ramification of processes.…”
Section: Discussionmentioning
confidence: 72%
“…Likewise, S3A silencing allows revascularization in ischemic tissues (Joyal et al, 2011). S3A also influences tumour cell migration and spreading in glioma (Bagci et al, 2009), therefore suggesting both autocrine and paracrine actions of S3A in brain tumours. Thus, these studies converge on the idea that restoring S3A expression might be of therapeutic interest to slow down tumour progression and aggressiveness.…”
Section: Discussionmentioning
confidence: 99%